Game of crowns : Elizabeth, Camilla, Kate, and the throne - Andersen, Christopher P. (Gallery Books, 2016)
Biographer "Christopher Andersen takes readers behind palace walls to examine the surprising similarities and stark differences among three remarkable women--Queen Elizabeth; Camilla, Duchess of Cornwall; and Princess Kate."--Book jacket.